Disparity in Constitutional Court Decisions Regarding the Age Limits for Presidential and Vice-Presidential Candidates (Study of Decision No. 29/PUU-XXI/2023 and Decision No. 90/PUU-XXI/2023 concerning the Age Limit for Presidential and Vice-Presidential Candidates) - Ashari, Ashari; Amalia, Riska Ari; Umam, Khairul; Kafrawi, Rachman Maulana (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The aim of this research is to determine the disparity in constitutional court decisions regarding the age threshold for presidential and vice-presidential candidates. This research is a type of normative legal research that uses statutory, conceptual and case approach methods. The results of the research explain that if examined from the aspect of considerations of constitutional court judges in case number 29/PUU-XXI/2023, it is stated that determining the minimum age of the President and Vice President is the domain of law makers (open legal policy), while in case number 90/PUU- XXI/2023 the constitutional court interpreted that the existence of an open legal policy (open legal policy) although it can be accepted in constitutional practice, but in its development the constitutional court could ignore or set aside while giving a re-interpretation of the norm which is an open legal policy, while from the adoption procedure decision in the judge's deliberative meeting held in case Number 29/PUU-XXI/2023, the chairman of the constitutional court, Anwar Usman, did not participate in discussing and deciding to avoid conflicts of interest, while in case Number 90/PUU-XXI/2023 with the same constitutionality issue the chairman The constitutional court participated in discussing and deciding the case with the decision being granted in part, namely being at least 40 years old or having/currently held a position elected through general elections, including regional head elections.